Strategi Pengendalian Biaya Operasional SMK: Antara Mutu dan Efisiensi Studi Kasus di SMK Negeri 1 Baso - Wetria; Hamdi Abdul Karim (Jurnal Salingka Nagari, 2026)
This study aims to analyze the strategies for controlling operational costs at SMK Negeri 1 Baso in maintaining a balance between educational quality and budget efficiency amid the demands of the Fourth Industrial Revolution and Society 5.0. The method used is descriptive qualitative research through a literature review approach, examining scientific journals, government policies, academic books, and regulations related to vocational education funding. The study findings indicate that the operational costs of vocational high schools are more complex than those of general schools due to the high demand for practical training facilities, consumables, facility maintenance, on-the-job training (OJT), and vocational competency tests (VCT). Effective cost control strategies include priority-based budget planning, efficient use of resources, diversification of funding sources, development of school production units, and strengthening partnerships with the business and industrial sectors (DUDI). The implementation of strategic cost management and Total Quality Management (TQM) has proven effective in maintaining the sustainability of educational quality without compromising budget efficiency. This study confirms that operational cost control is a strategic tool for improving the quality of vocational education. These findings are expected to serve as a reference for the development of adaptive, productive, and sustainable cost management in vocational high schools